2011
DOI: 10.2478/cttr-2013-0902
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Tobacco and Tobacco Smoke

Abstract: Tobacco and tobacco smoke are both complex mixtures. We previously reported 8430 unique chemical components identified in these complex mixtures but two years later our updated number was 8889. Addition of unlisted isomers raised these numbers to 8622 and 9081, respectively. Our previous number of 4994 identified tobacco components is now 5229; our previous number of 5315 identified tobacco smoke components is now 5685. An operational definition of a complex mixture is as follows: A complex mixture is a charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 49 publications
0
69
0
Order By: Relevance
“…However, these guidelines do not take into account aerosol exposure, nor indicate the nature that any alternative assessment procedures may take. Testing smoke aerosols in vitro is especially important when considering that there may be complex relationships between chemicals in each phase, semi-volatiles, short-lived products of combustion or unknown aerosol interactions within non-combustible products [20,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…However, these guidelines do not take into account aerosol exposure, nor indicate the nature that any alternative assessment procedures may take. Testing smoke aerosols in vitro is especially important when considering that there may be complex relationships between chemicals in each phase, semi-volatiles, short-lived products of combustion or unknown aerosol interactions within non-combustible products [20,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of these techniques are their relatively low time resolution and their specialisation in a few selected compounds such as carbon dioxide [21], acrolein or 1,3-butadiene [23]. Since tobacco smoke is a complex and reactive matrix containing over 5,600 identified compounds in vapour and particle phases [11,24,25], unravelling mechanistic information in real time requires a fast analysis technique. Time-of-flight mass spectrometry combined with photo ionisation has been proven to be capable of analysing cigarette smoke and other complex gas mixtures online with a high time resolution [10,[26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Carcinogenic metals, such as arsenic and cadmium, chromium, nickel, and lead (IARC, 2011) are mainly found in the particles (Slezakova et al, 2009a;Wu et al, 1997), as well as tobacco-specific nitrosamines (Thielen et al, 2008) and higher weight polycyclic aromatic hydrocarbons (Castro et al, 2011;Rodgman & Perfetti, 2006;Slezakova et al, 2009b). At present, as many as 570 PAHs have been identified in tobacco smoke (Perfetti & Rodgman, 2011), several of them being classified by the International Agency for Research on Cancer (IARC) as carcinogens (Rodgman & Perfetti, 2006, 2008. As most of these particulate-bound compounds have known adverse impacts on human health, the respective exposures represent a serious risk to human health (IARC, 2010;WHO, 2006).…”
Section: Tobacco Combustion and Compositionmentioning
confidence: 99%
“…Various authors reported that over 4000 different chemical components were found in tobacco smoke. However, in their last update Perfetti and Rodgman (2011) reported 5685 components in tobacco smoke that accounted for more than 99% of the mass of whole smoke. Certainly, other tobacco smoke components are present in the mixture but the total mass of these remaining components is obviously quite small (Perfetti & Rodgman, 2011).…”
Section: Tobacco Combustion and Compositionmentioning
confidence: 99%
See 1 more Smart Citation